Cartografias juvenis: mudanças e permanências nos territórios e modos de ser jovem - Carla Valeria Linhares Maia (2010)
This research had as objective to make a map and analyse to the juvenile existences and representations on being young and the youth universe in the students' of a public school of Belo Horizonte City, modality EYA Education of Youths and Adults. With that it intended to build cartography of the changes and permanence in the territoriesand manners of being young and the youth to live in different generations and historical contexts. The thesis resulted of aetnografy case study, close to students of different ages and youthful generations. For this purpose was developed a methodology that reconciled the synchronous perspective called the etnografy of intergeneration relationships observation in the space of the school , with the perspective diachronic through the mapping of the existences and juvenile territories, presents in your youth " reports. The study evidenced differences in the juvenile conditions put by the existences in different temporality, by the youth to live in the countryside or in the cities, or even for the you belong of gender, ethnic and social condition among other dimension.In a scenery marked by profound and accelerated transformations as the second half of the century XX and beginning of the century XXI, the research evidenced a compound movement between changes and permanence in the existences and juvenile condition, indicating the necessities of other studies that look for to still explore that juvenile diversity little explored by the academic researches on youths. Expectantly waits to have contributed, like this, with the production of the knowledge on youth and with the studies in the interface among Education, History and Anthropology.